PENGEMBANGAN WILAYAH KABUPATEN PANGANDARAN BERBASIS KOMODITAS UNGGULAN TANAMAN PANGAN - Hendriany, Reni; Pravitasari, Andrea Emma; Rustiadi, Ernan (Analisis Kebijakan Pertanian, 2024)
The District of Pangandaran is a new district in the Province of West Java. The agricultural sector is the main driver of economic growth in the District of Pangandaran. In the process of regional development, it is necessary to develop the potential of the area with a priority on the growing and unique sector and the identification of unique commodities as a basis for regional development policy. The objective of the research is to identify the unique agricultural crops in the District of Pangandaran and to identify the development areas based on the availability of facilities and infrastructure. The research was conducted in 2022. The type of data used is production data of food crops from 2018-2021, infrastructure data from the Pangandaran Agricultural Office and village potential data from the Central Bureau of Statistics. The method used is LQ and SSA and dendrogram. The results of the research show that the unique food crops in the District of Pangandaran are: Wetland Rice, Dryland Rice, Corn, Soybeans, Groundnuts, Green Beans, Cassava, and Sweet Potato. The dendrogram analysis shows that the Langkaplancar Sub-district and Padaherang Sub-district are in hierarchy 1. This means that both areas have the potential to become centers of activity for the development of food crop commodities because the facilities and infrastructure are relatively more complete than other areas. This analysis can provide a basis for determining more effective resource utilization policies for the development of unique commodities and with a focus on potential locations. This will increase production and productivity, ultimately improving the well-being of the community.